The Acute Coronary Syndrome Risk in Medically Managed Subjects with Type 2 Diabetes Mellitus : Is the ASCVD Risk Score Failing Here? - Joshi, Ameya; Singh, Harminder; Kalra, Sanjay (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Objectives. Type 2 Diabetics have elevated risk for acute coronary syndrome (ACS). The current management algorithm focuses on atherosclerotic cardiovascular (ASCVD) risk score to stratify this risk. However, in medically managed subjects, this algorithm may not be accurate. This study compares the ASCVD risk score in an Indian population with T2DM under medical supervision and the actual incidence of ACS. It also compared the ASCVD risk scores in cases with T2DM who developed ACS to controls and tried to estimate whether the ASCVD risk score is different in the two subsets, evaluating the utility of the ASCVD risk score in predicting ACS. Methodology. This is an electronic medical record (EMR) based case-control study. Only records of subjects with T2DM where details of age, sex, body mass index, blood pressure, duration of diabetes, family history of ACS, lipid profile, renal and liver function tests were included. The incidence of ACS was calculated in the selected records, and the records of subjects with ACS were compared with age and sex-matched subjects without ACS. Data are summarized as median and interquartile range (IQR). Wilcoxon rank-sum test was used for checking differences in continuous variables and Pearson’s Chi-squared test for categorical data. Univariate and multivariate logistic regression analyses were used to check the effect of ASCVD scores and other variables on the occurrence of ACS. Statistical data analyses were performed using JASP, version 0.16.4 (JASP Team [2022]) for MS Windows. Results. Of the 1226 EMRs included in the analysis, 207 had ACS. The actual incidence of ACS was 16.85% in 6 years, higher than the mean predicted 10-year incidence of 14.56 percent (p <0.05). The cases were age and sex-matched with controls and the ASCVD incidence was estimated in the two groups. The mean ASCVD score in the cases was 14.565 ± 8.709 (Min: 1.5, Max: 38.3) and controls 13.114 ± 8.247 (Min: 1.4, Max: 45). The chance of development of ACS increases with elevated systolic blood pressure (per mmHg rise OR: 1.04, 95% CI: 1.03, 1.06; p <0.001), positive family history (OR: 5.70, 95% CI: 3.41, 9.77; p <0.001), statin use (OR: 2.26, 95% CI: 1.46, 3.52; p <0.001), and longer duration of diabetes (for every year increase OR: 1.19, 95% CI: 1.13, 1.25; p <0.001) Conclusion. The ASCVD risk score underestimates the ACS risk in subjects with T2DM under medical supervision and may not differ in those who developed and did not develop ACS. We also conclude that factors like a negative family history (30% less risk), longer duration of diabetes, and higher SBP are relevant in those who developed ACS.